99mTechnetium‐pyrophosphate bone scan: A potential biomarker for the burden of transthyretin amyloidosis in skeletal muscle: A preliminary study. Issue 2 (31st October 2022) - Wlodarski, Richard; Seibert, Kaitlin; Issa, Naoum P.; O'Brien‐Penney, Bill; Soliven, Betty; Sarswat, Nitasha; Appelbaum, Daniel; Rezania, Kourosh
Abstract: Introduction/Aims: Transthyretin amyloidosis (ATTR) proteins can infiltrate skeletal muscle and infrequently cause a myopathy. 99m Technetium‐pyrophosphate ( 99m Tc‐PYP) is a validated biomarker for cardiac involvement in variant and wild‐type ATTR (ATTRv and ATTRwt, respectively). The aim of this study was to test the hypothesis that 99m Tc‐PYP is a biomarker for muscle burden of ATTR. Methods: Radioisotope uptake in the deltoid muscles of patients with ATTR was compared to uptake in control subjects without amyloidosis in a retrospective study. 99m Tc‐PYP scans were evaluated in 11 patients with ATTR (7 ATTRv, 4 ATTRwt) and 14 control subjects. Mean count (MC) values were measured in circular regions of interest (ROIs) 2.5–3.8 cm 2 in area. Tracer uptake was quantified in the heart, contralateral chest (CC), and deltoid muscles. Results: Tracer uptake was significantly higher over the deltoids and heart but not the CC, in patients with ATTR than in control subjects. MC values were 120.1 ± 43.7 (mean ± SD) in ATTR patients and 78.9 ± 20.4 in control subjects over the heart ( p  = 0.005), 73.3± 21.0 and 63.5 ± 14.4 over CC ( p  = 0.09), and 37.0 ± 11.7 and 26.0 ± 7.1 averaged over both deltoid muscles ( p  = 0.014). Discussion: 99m Tc‐PYP is a potential biomarker for ATTR amyloid burden in skeletal muscle. Abstract : See Editorial on pages 98‐100 in this issue